Overcoming Antimicrobial Resistance in Bacteria Using Bioactive Magnetic Nanoparticles and Pulsed Electromagnetic Fields - Novickij, Vitalij; Stanevičienė, Ramunė; Vepštaitė-Monstavičė, Iglė; Gruškienė, Rūta; Krivorotova, Tatjana; Sereikaitė, Jolanta; Novickij, Jurij; Servienė, Elena (Frontiers in Microbiology, 2018)
Nisin is a known bacteriocin, which exhibits a wide spectrum of antimicrobial activity, while commonly being inefficient against Gram-negative bacteria. In this work, we present a proof of concept of novel antimicrobial methodology using targeted magnetic nisin-loaded nano-carriers (iron oxide nanoparticles (11–13 nm) capped with citric, ascorbic and gallic acids), which are activated by high pulsed electric and electromagnetic fields allowing to overcome the nisin-resistance of bacteria. As a cell model the Gram-positive bacteria Bacillus subtilis and Gram-negative Escherichia coli were used. We have applied 10 and 30 kVcm-1 electric field pulses (100 µs x 8) separately and in combination with two pulsed magnetic field protocols: 1) high dB/dt 3.3 T x 50 and 2) 10 mT, 100 kHz, 2 min protocol to induce additional permeabilization and local magnetic hyperthermia. We have shown that the high dB/dt pulsed magnetic fields increase the antimicrobial efficiency of nisin nanoparticles similar to electroporation or magnetic hyperthermia methods and a synergistic treatment is also possible. The results of our work are promising for the development of new methods for treatment of the drug-resistant foodborne pathogens to minimize the risks of invasive infections.